2020
DOI: 10.1088/1361-6463/ab6519
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Komagataeibacter xylinus by a polarization modulation imaging method

Abstract: Komagataeibacter xylinus (K. xylinus) has been used for a long time as one of the main cellulose producers among bacterium. In order to gain a better understanding of the physiological and biochemical mechanisms of cellulose production, an efficient and noninvasive visualization method is highly demanded to monitor the morphological changes of K. xylinus during each stage of its development. In this study, a polarization parametric indirect microscopic imaging (PIMI) technique was applied to image the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recently, it has been demonstrated that the PIMI method, with its multi-parametric images, can be used to obtain rich detailed features of sub-cellular structures [27]. By measuring and filtering the distribution of the far-field optical scattering, PIMI can reveal high resolution nanoscale anisotropic structures using precisely modulated incident polarization [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the PIMI method, with its multi-parametric images, can be used to obtain rich detailed features of sub-cellular structures [27]. By measuring and filtering the distribution of the far-field optical scattering, PIMI can reveal high resolution nanoscale anisotropic structures using precisely modulated incident polarization [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have investigated the ability of polarization indirect microscopic imaging (PIMI) to resolve nano-features and molecular structures from the spatial polarization status distribution in the nano scattering field [15][16][17][18]. We also demonstrated that anisotropy in nanostructures can be identified from the scattered photon distribution [19,20]. Moreover, the PIMI scattering strength of viruses can be magnified by introducing an abrupt change of refractivity at the virus particle, enhancing the signal to the point where the presence of virus can be identified [21].…”
Section: Introductionmentioning
confidence: 99%
“…In our previously published papers, we have investigated the capability of polarization indirect microscopic imaging (PIMI) in resolving nano-features and molecular structures from the spatial polarization status distribution in the nano scattering field [19,20]. It is found that the polarization states of the photons can be used to map or image the anisotropic features of the nanostructure, with a resolving power beyond the diffraction limit of conventional microscopy, by detecting the variation of coupling and scattering photon states from the sample [21,22]. However, the scattering strength heavily depends on the change in refractivity in the near field under measurement.…”
Section: Introductionmentioning
confidence: 99%